Mechanistic study of surface functionalization of enzyme lysozyme synthesized Ag and Au nanoparticles using surface enhanced raman spectroscopy - Das, Raja; Jagannathan, Ramya; Sharan, Chandrashekhar; Kumar, Umesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
The fate of bioactivity of biomolecules such as enzymes, proteins, and even drug molecules is greatly affected by the conformational changes in the proximity of the solid surfaces. This interaction is the key to the potential of their further applications as biosensors, in drug delivery, etc. With increasing interest in the biofunctionalization of noble metal nanoparticles for various applications, it is important to precisely investigate the functional groups responsible for binding with the nanoparticle surfaces and probable structural changes in the structure of the biomolecules as both are key factors affecting the bioactivity of these molecules once they are tagged onto the nanoparticle surfaces. However, it is not an easy task to probe these properties, especially for bigger Molecules such as enzymes and proteins. Surface-enhanced Raman spectroscopy (SERS) has been used extensively in the detection of biomolecules and study of their conformation on noble metal surfaces since its discovery because of its high sensitivity. This technique is capable of detecting changes in the secondary structure and the effects of surrounding environment on the biomolecule in the proximity of nanoscopic rough metal surfaces. In this study, we have used this technique to precisely determine the functional groups responsible in the Surface capping of Ag and Au nanoparticles synthesized by the hen egg derived enzyme lysozyme. The sharp and intense Stokes Raman shift peaks observed around 704, 866, 1519, and 1598 cm(-1), in the case of Ag nanoparticles, which are assigned to tryptophan, tyrosine, phenylalanine, and histidine residues, clearly indicate the involvement of these residues for surface passivation of the Ag nanoparticle surface. The Ag-N peak situated around 236 cm(-1) was also seen in the spectra, showing that probably the amine group of lysozyme is responsible in binding to the Ag nanoparticle surface. Similarly, in the case of Au nanoparticles, we observed sharp and intense peaks around 1583, 1545, and 1584 cm(-1) which were assigned to above-mentioned amino acid residues, indicating that a similar mechanism is also responsible for the binding of lysozyme molecules at the Au nanoparticle surface. In both cases peaks for the amide III band (C-N-H) around 1250 cm(-1) were also observed.

Modulation and optimization of drug release from uncoated low density porous carrier based delivery system - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Poddar, Pankaj; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The purpose of this research work was to explore an application of uncoated porous drug carrier prepared by single-step drug adsorption for a delivery system based on integration of floating and pulsatile principles intended for chronotherapy. This objective was achieved by utilizing 3(2) factorial design, solvent volume (X (1)) and drug amount (X (2)) as selected variables, for drug adsorption using solvents, methanol, and dichloromethane (DCM), of varying polarity. Nitrogen adsorption (N(2)), scanning electron microscopy of cross-sections, and atomic force microscopy were done to study adsorption patterns and their effect on release pattern. Drug release study was customized by performing for 6 h in acidic environment to mimic gastroretention followed by basic environment akin to transit phase. Correlation between porous data from mercury and N(2) adsorption was probably studied for the first time. Observed regression analysis values for pore volume, surface area, and drug release indicated the influence of selected variables. Total release range in acidic medium was 12.77-24.57% for methanol, 8.79-15.26% for DCM, and final release of 69.45-92.23% for methanol, and 60.16-99.99% for DCM influenced by varying internal geometries was observed. Present form of drug delivery system devoid of any additives/excipients influencing drug release shows distinct behavior from other approaches/technologies in chronotherapy by (a) observing desired low drug release (8%) in acidic medium, (b) overcoming the limitations of process variables caused by multiple formulation steps and different characteristic polymers, (c) reducing time consumption due to single step process, and (d) extending as controlled/extended release.
Keywords: chronotherapy; floating pulsatile drug delivery system; low density porous carrier; pore data; solvent polarity

Magnetic and dielectric properties and Raman spectroscopy of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Vivekanand, K.; Maity, Tuhin; Abraham, Priya Mary; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Applied Physics, 2010)
The rare earth orthochromites are extremely interesting due to the richness of their optical, dielectric, and magnetic properties as well as due to their multiferroic properties which make them suitable materials to study in the nanoregime. However, the wet-chemical synthesis of these materials in nanosize is nontrivial. Here, we report for the first time, the detailed Raman spectra as well as magnetic and dielectric properties of chemically synthesized GdCrO3 nanoparticles of size ranging from 40 to 60 nm. The magnetic properties are dictated by competing Cr3+-Cr3+, Gd3+-Cr3+, and Gd3+-Gd3+ superexchange interactions in different temperature regions, resulting into an antiferromagnetic ordering at 167 K due to the Cr3+-Cr3+ followed by weak ferromagnetic ordering due to the onset of Cr3+-Gd3+ interactions. At lower temperature, it shows weak antiferromagnetic ordering due to Gd3+-Gd3+ interaction. Below 95 K, GdCrO3 nanoparticles showed the presence of negative magnetization due to Gd3+ and Cr3+ interactions resulting into weak ferromagnetic coupling. The Raman spectroscopy shows the characteristic Raman shifts indicating that below 450 cm(-1), Gd3+ ions play a dominant role in determining the phonon frequencies of GdCrO3, and above 450 cm(-1), the Cr+3 ions dominate. We also present for the first time the low temperature dielectric constant and loss tangent data for GdCrO3 in a broad temperature and frequency range. The dielectric constant shows a decrease in comparison to the bulk values due to the size dependent effects. It also shows a peak centered at around 320 K above which it shows a sharp decrease. The dielectric loss value in GdCrO3 nanoparticles is quite small and shows an interesting frequency dependent anomaly at lower temperature which might be due to the coupling between magnetic and dielectric order parameters.
Keywords: dielectric losses; gadolinium compounds; Magnetisation; Multiferroics; nanofabrication; Nanoparticles; permittivity; phonons; Raman spectra; superexchange interactions

Metal and metal oxide nanoparticle synthesis from metal organic frameworks (MOFs): finding the border of metal and metal oxides - Das, Raja; Pachfule, Pradip; Banerjee, Rahul; Poddar, Pankaj (Nanoscale, 2012)
Herein, for the first time, we report a generalized strategy for the successful synthesis of highly crystalline metal and metal oxide nanoparticles embedded in a carbon matrix by the controlled thermolysis of metal organic frameworks (MOFs). The rationalized synthesis strategy of a broad range of metal and metal oxides nanoparticles, such as Cu/CuO, Co/Co3O4, ZnO, Mn2O3, MgO and CdS/CdO, by thermolysis of MOFs demonstrates for the first time that metal ions with a reduction potential of -0.27 volts or higher present in MOFs always form pure metal nanoparticles during thermolysis in N-2, whereas metal ions with a reduction potential lower than -0.27 volts form metal oxide nanoparticles during thermolysis in N-2. Another point of interest is the fact that we have found a unique relationship between the nanoparticle size and the distance between the secondary building units inside the MOF precursors. Interestingly, the crystallinity of the carbon matrix was also found to be greatly influenced by the environment (N-2 and air) during thermolysis. Moreover, these nanoparticles dispersed in a carbon matrix showed promising H-2 and CO2 adsorption properties depending on the environment used for the thermolysis of MOFs.

Modification of crystal anisotropy and enhancement of magnetic moment of Co-doped SnO2 thin films annealed under magnetic field - Loya-Mancilla, Sagrario M.; Poddar, Pankaj; Das, Raja; Ponce, Hilda E. Esparza; Templeton-Olivares, Ivan L.; Solis-Canto, Oscar O.; Ornelas-Gutierrez, Carlos E.; Espinosa-Magaa, Francisco; Olive-Mendez, Sion F. (Nanoscale Research Letters, 2014)
Co-doped SnO2 thin films were grown by sputtering technique on SiO2/Si(001) substrates at room temperature, and then, thermal treatments with and without an applied magnetic field (H-TT) were performed in vacuum at 600 degrees C for 20 min. H-TT was applied parallel and perpendicular to the substrate surface. Magnetic M(H) measurements reveal the coexistence of a strong antiferromagnetic (AFM) signal and a ferromagnetic (FM) component. The AFM component has a N,el temperature higher than room temperature, the spin axis lies parallel to the substrate surface, and the highest magnetic moment m =7 mu(B)/Co at. is obtained when H-TT is applied parallel to the substrate surface. Our results show an enhancement of FM moment per Co+2 from 0.06 to 0.42 mu(B)/Co at. for the sample on which H-TT was applied perpendicular to the surface. The FM order is attributed to the coupling of Co+2 ions through electrons trapped at the site of oxygen vacancies, as described by the bound magnetic polaron model. Our results suggest that FM order is aligned along [101] direction of Co-doped SnO2 nanocrystals, which is proposed to be the easy magnetization axis.
Keywords: Antiferromagnetism; Crystal anisotropy; Diluted magnetic oxide; Ferromagnetism; Magnetic anisotropy; Magnetic moment; Spin axis; thin film

Modulation of reaction kinetics for the tuneable synthesis of gold nanoparticles and quantum clusters: application of gold quantum clusters as ``turn-off'' sensing probe for Sn4+ ions - Khandelwal, Puneet; Singh, Dheeraj K.; Sadhu, Subha; Poddar, Pankaj (ChemPlusChem, 2014)
The syntheses of gold nanoparticles (Au NPs) and gold quantum clusters (Au QCs) that employ cefadroxil (CFX; an antibiotic) as both reducing and capping agents are reported. The HAuCl4/CFX concentration, temperature, and pH are crucial factors in the modulation of the nucleation and growth kinetics of the reaction, and consequently, in guiding the size and morphology of as-synthesized Au NPs. Interesting results are observed if the reaction is performed under different pH conditions. TEM analysis of the Au NPs synthesized at pH 6 shows an average particle size of approximately 2 nm along with a relatively smaller population of bigger NPs (up to 6 nm). The Au QCs were isolated by high-speed centrifugation and showed fluorescence at lambda approximate to 460 nm. Furthermore, the as-synthesized Au QCs were applied as sensor for Sn4+ ions on the basis of an aggregation-induced fluorescence quenching mechanism. These Au QCs offer acceptable sensitivity, high selectivity, and a limit of detection of approximately 10 mm for the determination of Sn4+ ions.

Mechanistic insight into the biomilling of goethite (alpha-FeO(OH)) nanorods using the yeast Saccharomyces cerevisiae - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
Since the last decade, eco-friendly routes for the synthesis of nanostructured materials of various types and functionalities have been a topic of enormous interest in the field of nanotechnology. The primary work in this field started with the `bottom-up' microbial synthesis of nanoparticles, however, the bioleaching potential of microbes was initially overlooked in this research. The bioleaching process is useful especially where the synthesis of particles with size < 10 nm is challenging. In the present work, the mechanistic insight of biomilling for a gradual transformation of anisotropic alpha-FeO(OH) rod-shaped particles into isotropic nanoparticles below 10 nm size has been explored using detailed UV-vis spectroscopy, transmission electron microscopy, atomic force microscopy, X-ray diffraction, and X-ray photoelectron spectroscopic studies which suggest that the aquo group present at the alpha-FeO(OH) surface may provide the site for interaction with carboxyl ions of protein molecules which results in the formation of a stable coordination compound with Fe3+ ions. This will create a new Fe3+ ion on the surface of the lattice which leads to the repetition of the process of protein complexation with Fe3+ ions and dissociation of the complex from the lattice that causes the fragmentation of bigger nanoparticles into protein functionalized smaller nanoparticles.